1994
DOI: 10.1177/088307389400900104
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Biopterin and Homovanillic Acid Levels in Cerebrospinal Fluid From Children With Aseptic Meningitis

Abstract: To examine biopterin fractions and biogenic amine metabolites in cerebrospinal fluid in aseptic meningitis, the concentrations of homovanillic acid, 5-hydroxyindoleacetic acid, and the total, the oxidized form, and the reduced form of biopterin were determined in cerebrospinal fluid specimens from 15 children with aseptic meningitis in the acute phase, 15 children with aseptic meningitis in the recovery phase, and six other children as controls. The concentration of each substance was significantly higher in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The CSF levels of each metabolite observed in the present study were similar to those reported previously (9)(10)(11)(12). We added the data from the patients with aseptic meningitis in recovery phase to those of the controls because we previously determined that the levels of biopterin and biogenic amine metabolites in patients with aseptic meningitis in recovery phase are comparable to those of controls (7).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The CSF levels of each metabolite observed in the present study were similar to those reported previously (9)(10)(11)(12). We added the data from the patients with aseptic meningitis in recovery phase to those of the controls because we previously determined that the levels of biopterin and biogenic amine metabolites in patients with aseptic meningitis in recovery phase are comparable to those of controls (7).…”
Section: Discussionsupporting
confidence: 88%
“…Samples were assayed within 1 mo of collection. CSF levels of biopterin, HVA and 5-HIAA were determined by high-performance liquid chromatography, as described previously (7). Data were analysed using the SAS/STAT system for personal computers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…0.4ml CSF or 0.3ml serum was collected into a tube containing iodine in 0.1N HC1 or 0.1N NaOH, shaken, and stored at -80~ until assay. After each sample was subjected to partial purification on a Dowex 50 column, it was injected into a high performance liquid chromatograph (Komori et al, 1994). The sample after acid oxidation represents the total biopterin (total B; BH4, quinonoid dihydrobiopterin, BH2, and biopterin), and the sample after alkaline oxidation represents the oxidized form of biopterin (oxidized B; BH2 and oxidized biopterin).…”
Section: Biopterin Assay Biogenic Amine and Folate Measurementsmentioning
confidence: 99%
“…• regulation of enzyme activity (i.e., phosphorylation) and other minor interactions, such as the regulatory action of serotonin turnover on dopamine turnover, the latter helps explain the interdependence of 5-HIAA and HVA in CSF (11,12); • availability of amino acid precursors (13) and transport; impaired transport of tyrosine and tryptophan has been implicated in aminoamine disturbances in schizophrenia (14), HIV infection (15) and untreated phenylketonuria (16); • inter-individual genetic heterogeneity (17) due to DNA polymorphism in genes of enzymes involved in the synthesis and catabolism of monoamines; • rate of reuptake/egress: variability between individuals in the transport process (probenecid-sensitive organic anion transport system) may also contribute to the variability of lumbar HVA and 5-HIAA concentrations; • rate of CSF formation.…”
Section: Metabolism Of Monoaminesmentioning
confidence: 99%